2023
DOI: 10.3390/polym15122628
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Iron Phosphate/Carbon (LFP/C) Composite Using Nanocellulose as a Reducing Agent and Carbon Source

Abstract: Lithium iron phosphate (LiFePO4, LFP) is the most promising cathode material for use in safe electric vehicles (EVs), due to its long cycle stability, low cost, and low toxicity, but it suffers from low conductivity and ion diffusion. In this work, we present a simple method to obtain LFP/carbon (LFP/C) composites with different types of NC: cellulose nanocrystal (CNC) and cellulose nanofiber (CNF). Microwave-assisted hydrothermal synthesis was used to obtain LFP with nanocellulose inside the vessel, and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The organic carbon source can be decomposed to form carbon monomers, which are then attached to the surface of the LFP particles during the heat treatment process. Studies have suggested that in situ coating is more effective than ex situ coating with the direct addition of carbon materials [ 16 , 17 , 18 , 19 ]. The carbon sources used for carbon coatings are mainly organic carbon sources, including glucose, sucrose, citric acid, and cotinine black.…”
Section: Introductionmentioning
confidence: 99%
“…The organic carbon source can be decomposed to form carbon monomers, which are then attached to the surface of the LFP particles during the heat treatment process. Studies have suggested that in situ coating is more effective than ex situ coating with the direct addition of carbon materials [ 16 , 17 , 18 , 19 ]. The carbon sources used for carbon coatings are mainly organic carbon sources, including glucose, sucrose, citric acid, and cotinine black.…”
Section: Introductionmentioning
confidence: 99%